Preventive Strategies for Citizen Security: A Comparative Analysis of International and National Models - Mg. Shakespeare Voltaire Cruz Ipanaqué, Dr. Rafael Damián Villón Prieto Ipanaqué, Mg. María Consuelo Tapia Martinez, Mg. Jahaira Viviana Nuñez Jimenez, Mg. Ida Blanca Pacheco Gonzales (South Eastern European Journal of Public Health, 2024)
The general objective of this research was to understand the scientific evidence on preventive strategies for citizen security. A qualitative approach and a literature review were used, covering national and international studies. The instruments applied included content analysis of scientific publications. The main results indicated that preventive strategies, such as community participation, environmental design and increased police presence, are effective in reducing crime. In the United States and the United Kingdom, community integration in security programs has shown positive results; in Peru, police modernization and the implementation of technologies have improved the response to security incidents. The main conclusion is that the implementation of evidence-based preventive strategies can significantly improve citizen security and the perception of security.